Peasant territories in resistance: the agroecological farm experience of Asopasquillita, Colombia - García Briñez, Nasly Tatiana (2025)
Territorial defense has become a central strategy for rural communities in Colombia in response to historical pressures that reshape their social, economic, cultural, and environmental dynamics. This article examines the territorial resistance practices promoted by the Association of Peasants for Sustainable Development of the Pasquillita village (Asopasquillita), located in the rural area of Bogotá, in the face of urban expansion, exclusionary rural development policies, and the increasing precariousness of peasant life. Drawing on a qualitative and ethnographic methodology—based on in-depth interviews, participant observation, and analysis of both community and official documents—this study analyzes how Asopasquillita articulatesstrategies of re-existence that integrate associativity, rural education, agroecology, environmental stewardship, and dynamics of gender and identity. It argues that these practices enable a contestation of dominant development logics, while also shaping alternative ways of inhabiting and sustaining life from a Food Sovereignty perspective. This study contributes to current debates on contemporary ruralities as contested spaces, where collective subjects emerge to construct meanings, knowledge,and practices aimed at fostering more autonomous, sustainable, and territorially rooted ways of life, within a context of increasing tensions generated by globalization.